Revenge as Seen in Mary Shelley’s Frankenstein; or, The Modern Prometheus - Tini Mogea (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2023)
This research is to find out how revenge is revealed in Mary Shelley’s Frankenstein, or The Modern Prometheus. This research is qualitative since the data are in the form of words rather than numbers. The data were collected in the novel Frankenstein, or The Modern Prometheus. An objective approach is used in analyzing the data. The result shows that the formula of a mystery shows that the problem always has a desirable and rational solution, but the mystery being or state is not resolved. The first formula; the problem always has a desirable and rational solution, is the Frankenstein solution to find eternal life, such as by doing further research, following the guidelines of a book by scientists, studying the branches of science related to research, identifying laboratory equipment, making the design and size of the body resemble the human body, and even collecting human bones that have been dead. The second formula, that the mystery of the imaginary being or state is not resolved, is Frankenstein’s failure to control the monster. As a creator, Frankenstein should be able to control his creation. But the reality is that he is not capable.